Paying health care providers in the Caribbean - Pinto, Matilde (PAHO WashingtonUS, 2001)
Focuses on payment mechanisms to hospitals, physicians and health centres. Proposes some steps that can be taken if countries decide to pursue the subject of provider payment mechanisms.